Community development and propulsion mechanism with the sustainability and co-creation: Sawankhalok master plan for tourism activities in world heritage areas of historical districts Sukhothai Si Satchanalai and Kamphaeng Phet - Surasak Kangkhao (My University, 2020)
This research investigated, analysis, and survey on the satisfactory levels of local organizations and community leaders in Sawankhalok district with a proposed master plan to develop strategic models for creative tourism. Situated in Sukhothai province, the area sheltered Sawankhalok—Si Satchanalai Historical Park, one of UNESCO World Heritage sites in Thailand. Linked to the objectives of sustainability and co-creation of the United Nations, to improve the quality of life and sustainable economy while seeking to recover the historical link among culture, co-creation development, and sustainability while the area is currently represented in a state of fragment and disconnect between three important areas. Based on this context, this paper analyzes the main problems and studies through “Cs” Coordination, Cooperation, and Collaboration strategy method and interviewing on focus group and future procedure. After the implementation and operational framework on the Sawankhalok Master plan for Tourism journey in World Heritage areas of Historical districts Sukhothai—Si Satchanalai and Kamphaeng Phet, the result shows that the plans and projects were able to develop the management on the cultural and historical tourism while creating a common ground for multi-parties in the area. Similarly, the strategic drafting found that the vision of the Sukhothai and associate towns World Heritage was to sustainably and co-creation the values of the Sukhothai and associate towns World Heritage.
Keywords: Heritage Tourism; Diverse Aspects of Tourism Research